2017
DOI: 10.1016/j.celrep.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Laminin Levels Regulate Tissue Migration and Anterior-Posterior Polarity during Egg Morphogenesis in Drosophila

Abstract: SummaryBasement membranes (BMs) are specialized extracellular matrices required for tissue organization and organ formation. We study the role of laminin and its integrin receptor in the regulation of tissue migration during Drosophila oogenesis. Egg production in Drosophila involves the collective migration of follicle cells (FCs) over the BM to shape the mature egg. We show that laminin content in the BM increases with time, whereas integrin amounts in FCs do not vary significantly. Manipulation of integrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…Laminins have been found to be necessary for tissue morphogenesis (reviewed in Miner and Yurchenco ) and function in developmental processes such as egg chamber elongation, egg shape determination (Andersen and Horne‐Badovinac ), cell migration, induction, and maintenance of cell polarity (Diaz de la Loza et al. ) and glial cell development (Yu et al. ; Petley‐Ragan et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laminins have been found to be necessary for tissue morphogenesis (reviewed in Miner and Yurchenco ) and function in developmental processes such as egg chamber elongation, egg shape determination (Andersen and Horne‐Badovinac ), cell migration, induction, and maintenance of cell polarity (Diaz de la Loza et al. ) and glial cell development (Yu et al. ; Petley‐Ragan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ovaries of LanB2 depleted mutant flies contain aberrant follicle cells and rounded eggs (Diaz de la Loza et al. ), which might have an impact on egg laying rate and thus egg retention. We further found that 5/15 associated genes have highest adult expression in ovaries (Table S3A, B), and are functioning as early gene expression regulators ( vfl ), in repair mechanisms ( spel1 ), and oligosaccharide biosynthesis ( Pgant35A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the importance of the BM membrane structure and stiffness to elongate the follicle and the egg (Denef et al, 2008;Díaz de la Loza et al, 2017;Haigo and Bilder, 2011;He et al, 2010;Horne-Badovinac, 2015, 2016;Lerner et al, 2013;Schneider et al, 2006;Viktorinová and Dahmann, 2013). Two non-exclusive models have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…BM is an ancient and highly conserved ECM that lines the basal surface of epithelial and endothelial tissues and surrounds muscles, adipose tissue, and nerves [26, 28,29]. Studies using Drosophila have made particularly strong contributions to our understanding of BM secretion and assembly [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and the role BMs play in shaping tissues during development [35,42,[46][47][48][49][50][51][52][53]. They have also shown how BMs heal after injury [54,55] and how they regulate the immune response [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%